(untitled) (Bangladesh Critical Care Journal, 2023)
Background: Early pregnancy loss is one of the most common clinical problems that is encountered in daily gynaecological practice. The aim of this study is to assess the effectiveness and acceptability of using vaginal misoprostol for management of first trimester spontaneous incomplete abortion as an alternative to direct vaginal surgical evacuation in our setting. Methods: This prospective randomized study was carried out in the Department of Obstetrics and Gynaecology in Shaheed Ziaur Rahman Medical College Hospital, Bogra. from January 2008 to December 2008. This study performed on 400 patients with first trimester incomplete abortion between 8 and 12 weeks requesting medical management. They were divided into two groups according to patients’ choice; group (I) received 800 microgram misprostol vaginally by digital insertion into the posterior fornix while group (II) underwent surgical vaginal evacuation directly under general anesthesia. Results: Although vaginal surgical evacuation was successful in solving the problem in 100% of cases, misoprostol was successful in 70% after 1st dose and remained incomplete 30% after administration of 2nd dose. The overall satisfaction was slightly higher in the surgical group. No serious side effects or complications were reported in the misoprostol group. The incidence of excessive post-abortive bleeding was more in the misoprostol group than in the surgical evacuation group (p = 0.049). Conclusion: Although vaginal surgical evacuation is more effective than misoprostol in solving the problem still medical treatment is effective and acceptable especially when surgical management is not available or risky or patients refuse to do surgical management. Bangladesh Crit Care J March 2023; 11 (1): 19-23